2016
DOI: 10.1038/srep21587
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of rAAV2-ND4 Treatment for Leber’s Hereditary Optic Neuropathy

Abstract: Leber’s hereditary optic neuropathy (LHON) is a mitochondrially inherited disease leading to blindness. A mitochondrial DNA point mutation at the 11778 nucleotide site of the NADH dehydrogenase subunit 4 (ND4) gene is the most common cause. The aim of this study was to evaluate the efficacy and safety of a recombinant adeno-associated virus 2 (AAV2) carrying ND4 (rAAV2-ND4) in LHON patients carrying the G11778A mutation. Nine patients were administered rAAV2-ND4 by intravitreal injection to one eye and then fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 28 publications
3
114
0
16
Order By: Relevance
“…Lastly, aiming at mitochondrial delivery of a normal mtDNA-encoded ND4 protein, allotopic expression has been attempted in patients with LHON, despite controversial preclinical results. One trial (NCT01267422) has been recently completed and has shown significant improvement of visual acuity and enlargement of visual field in the treated group (32). Two additional trials are underway (NCT02161380; NCT02064569).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Lastly, aiming at mitochondrial delivery of a normal mtDNA-encoded ND4 protein, allotopic expression has been attempted in patients with LHON, despite controversial preclinical results. One trial (NCT01267422) has been recently completed and has shown significant improvement of visual acuity and enlargement of visual field in the treated group (32). Two additional trials are underway (NCT02161380; NCT02064569).…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Using pretherapy VA as the baseline, BCVA was examined using a standard logMAR acuity chart at a distance of 2.5 m (Star Kang Medical Technology Co., Ltd. Wen Zhou, China) [8, 9]. The same ophthalmologists examined the BCVA of both injected and uninjected eyes in 7 patients before gene therapy, and at 3, 6, 9, 24, and 36 months after treatment.…”
Section: Methodsmentioning
confidence: 99%
“…We used gene therapy for the treatment of 9 patients with LHON from 2011 to 2012 (Trial registry: Safety and efficacy study of a single intravitreal injection of rAAV2-ND4 treatment of Leber’s hereditary optic neuropathy; No. NCT01267422; December 2010), with clinical follow-up observation of changes in VA and VF values at different time points [8, 9]. We found that patients with LHON who received a monocular intravitreal injection of AAV2-ND4 and exhibited enhanced VA actually demonstrated VA improvement in both injected and uninjected eyes, or exhibited significant VA improvement in one eye and some improvement in the other eye.…”
Section: Introductionmentioning
confidence: 99%
“…53,54 Advances are also being made in RGC disease and clinical trials are currently being conducted to evaluate the efficacy of GS010, an adeno-associated virus type 2 (AAV2) construct containing the human wild-type NADH dehydrogenase subunit 4 (ND4) gene to treat patients with Leber's Hereditary Optic Neuropathy due to the G11778A ND4 mitochondrial mutation. Preliminary data from the Phase I/II trial 55,56 showed promising results and provided the foundation for two Phase III clinical trials which are currently underway. 57,58 Additional gene-based strategies being investigated include the delivery of genes encoding therapeutic proteins such as neurotrophic factors.…”
Section: Gene Therapymentioning
confidence: 99%